2014
DOI: 10.1007/s11145-014-9538-8
|View full text |Cite
|
Sign up to set email alerts
|

The developmental trend of orthographic awareness in Chinese preschoolers

Abstract: The present study explored the developmental trend of orthographic awareness in Chinese-speaking preschoolers. A total of 184 children between 3 and 5 years of age participated in the study. Two developmental patterns of orthographic awareness were obtained. One pattern was dependent on a traditional Chinese orthographic hierarchy, with a sequence of writing system specificity, radical, whole character, radical combination rules, and stroke. Three-year-olds fully understood the writing-system-specific features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 39 publications
(72 reference statements)
2
18
0
Order By: Relevance
“…The written words of a language can be conceptualized as patterns of letters rather than as representations of language, and early learning of graphotactic patterns seems to occur in similar ways for children exposed to a shallower alphabetic writing system, Portuguese, and children exposed to a deep alphabetic writing system, English. Indeed, some findings suggest that learning of visual patterns occurs in similar ways in Chinese, which differs substantially from alphabetic writing systems in how it represents language (e.g., Luo, Chen, Deacon, & Li, 2011; Qian, Song, Zhao, & Bi, 2015; Tong & McBride-Chang, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…The written words of a language can be conceptualized as patterns of letters rather than as representations of language, and early learning of graphotactic patterns seems to occur in similar ways for children exposed to a shallower alphabetic writing system, Portuguese, and children exposed to a deep alphabetic writing system, English. Indeed, some findings suggest that learning of visual patterns occurs in similar ways in Chinese, which differs substantially from alphabetic writing systems in how it represents language (e.g., Luo, Chen, Deacon, & Li, 2011; Qian, Song, Zhao, & Bi, 2015; Tong & McBride-Chang, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Children gradually get access to, understand, and build morphemic knowledge during the learning process. Visual-spatial skills (Lin, Sun, & Zhang, 2016), orthographic awareness (e.g., Qian, Song, Zhao, & Bi, 2015), and phonological awareness (e.g., Li et al, 2012) have been found to be significant predictors of Chinese reading development in previous studies, given the heavy reliance on visual-orthographic information for learning of the Chinese script and the activation of phonological information in Chinese reading. Nonverbal IQ was included in the study as a general cognitive control for reading ability (e.g., McBride-Chang et al, 2003;Tong et al, 2011).…”
Section: The Present Studymentioning
confidence: 91%
“…Nonverbal IQ was included in the study as a general cognitive control for reading ability (e.g., McBride-Chang et al, 2003;Tong et al, 2011). Visual-spatial skills (Lin, Sun, & Zhang, 2016), orthographic awareness (e.g., Qian, Song, Zhao, & Bi, 2015), and phonological awareness (e.g., Li et al, 2012) have been found to be significant predictors of Chinese reading development in previous studies, given the heavy reliance on visual-orthographic information for learning of the Chinese script and the activation of phonological information in Chinese reading. These variables were included in the study.…”
Section: The Present Studymentioning
confidence: 99%
“…We therefore provide evidence, stronger than that presented by Qian et al . (), that Chinese children as young as 3 years know about some general graphic characteristics of their writing system. Such graphic knowledge appears to emerge in learners of Chinese at similar ages as in learners of alphabetic writing systems (Lavine, ; Treiman et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to outer form, we know of only one study to have tested Chinese‐speaking children younger than 5 years. In this study, Qian, Song, Zhao, and Bi () asked 3‐ to 5‐year‐olds whether various displays, including common Chinese characters, pictures, and English words, were well‐written Chinese characters. Qian et al .…”
Section: Introductionmentioning
confidence: 99%